2014
DOI: 10.1128/jvi.02232-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Anti-Spike Protein Receptor Binding Domain Antibodies on Severe Acute Respiratory Syndrome Coronavirus Neutralization Escape and Fitness

Abstract: The receptor binding domain (RBD) of the spike (S) glycoprotein of severe acute respiratory syndrome coronavirus (SARS-CoV) is a major target of protective immunity in vivo. Although a large number of neutralizing antibodies (nAbs) have been developed, it remains unclear if a single RBD-targeting nAb or two in combination can prevent neutralization escape and, if not, attenuate viral virulence in vivo. In this study, we used a large panel of human nAbs against an epitope that overlaps the interface between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 55 publications
8
96
0
Order By: Relevance
“…A combination of two neutralizing mAbs could prevent the emergence of neutralization escape mutants or at least attenuate viral virulence in vivo. However, although neutralizing mAbs directed against epitopes located at the interface between the viral S protein and its cellular receptor, angiotensin-converting enzyme 2 (ACE2), proved to have great potency and breadth in neutralizing multiple viral strains (Sui et al, 2014), both the single and combined use of one or two mAbs, respectively, failed to prevent the emergence of antibody escape variants. Therefore, the use of one or two neutralizing mAbs that target a structurally flexible SARS-CoV epitope may be of limited value for in vivo immunotherapies and should be combined with neutralizing mAbs that bind a second conserved epitope with low structural plasticity.…”
Section: Antigenic Complexity Of Sars-and Mers-covmentioning
confidence: 99%
“…A combination of two neutralizing mAbs could prevent the emergence of neutralization escape mutants or at least attenuate viral virulence in vivo. However, although neutralizing mAbs directed against epitopes located at the interface between the viral S protein and its cellular receptor, angiotensin-converting enzyme 2 (ACE2), proved to have great potency and breadth in neutralizing multiple viral strains (Sui et al, 2014), both the single and combined use of one or two mAbs, respectively, failed to prevent the emergence of antibody escape variants. Therefore, the use of one or two neutralizing mAbs that target a structurally flexible SARS-CoV epitope may be of limited value for in vivo immunotherapies and should be combined with neutralizing mAbs that bind a second conserved epitope with low structural plasticity.…”
Section: Antigenic Complexity Of Sars-and Mers-covmentioning
confidence: 99%
“…For instance, its large parts are cleaved during infection by cellular proteases and expose the receptors to activate viral attachment to the host (Fiscus, 1987;Wu et al, 2004aWu et al, , 2004bMaache et al, 2006;Gao et al, 2013). Additionally, the S protein is prone to mutations, especially in the amino acids associated with the spike protein-cell receptor interface, in order to overcome host immunity (Wu and Yan, 2005;Sui et al, 2014). In an interesting study, the N gene of the CoV was found to be more effective for evaluating the codon usage bias than the S gene (Ahn et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the variability in the amino acid sequence of the spike protein observed among MERS-CoV strains is low [71], and circulating MERS-CoV strains did not show any significant variation in the serological reactivity [25,59], implying that the development of a vaccine that is effective against one strain is likely to be protective against all circulating strains. Another risk posed from the development of antibody escape variants is still present [72,73], although this is not likely to happen as mutations in two epitopes may be required, and mutants that develop may have reduced viral fitness [73,74].…”
Section: Challenges and Novel Approaches For Cov Vaccinesmentioning
confidence: 99%